High stability in color chromaticity of warm white emitting diode with dual-hue SrSi2O2N2:Eu2+,Yb2+ phosphor - My Hanh Nguyen Thi; Phan Xuan Le; Nguyen Le Thai (Institute of Advanced Engineering and Science, 2022)
In this study, we analyzed and developed a phosphor with a nitridiosilicate based and emitting color changing from green to orange to apply to our white-light-emitting diodes (WLEDs). Eu2+ and Yb2+ trap sites of two-doped SrSi2O2N2:Eu2+,Yb2+ (SrYb) nitridosilicate emit a wide emission in the region between green and orange. Through calculating the decompose time of the green-emission power donor, we could determine the converted energy between the active ions. Furthermore, we also analyzed the impact of co-doping with varied active ion ratios on the photoluminescence (PL) characteristics. As the concentration of Yb2+ increases, the red emission dominates the green. This was because the obtained phoshor's emission depended on the activator ion components. To generate white light, a combination of the acquired phosphor and the InGaN blue LED chip with a 450 nm wavelength was used. With only two steps, we could detect the hue balance management. Firstly, by modifying the Eu2+ and Yb2+ concentration, we can conduct a green-to-orange proportion optimization. Following that, the commission onillumination (CIE) coordinates were transformed to [0.4071; 0.3789] from the original position, which was [0.2805; 0.2014] by enhancing the phosphor powder amount. An environment which has a CRI of around 89 is the optimum condition for conducting white light.